Saliva protection and transmissible diseases - Posse, Jacobo Limeres; Dios, Pedro Diz; Scully, Crispian (London Elsevier/Academic Press, 2017)
Saliva Protection and Transmissible Diseases provides a review of saliva protection, raising debate on micro-organisms potentially transmissible in saliva, and also considering the evidence on diseases that may be transmitted by kissing. Saliva is a complex body fluid essential to health, especially mastication, swallowing and speech, and hyposalivation can lead to dysfunction and even infection. More serious pathogens, such as herpes viruses and papillomaviruses can be conveyed by kissing, as can potentially lethal micro-organisms present in some saliva, such as meningococci, fungal organisms and Ebola viruses.--Provided by publisher.
Chapter 1 - Infection Transmission by Saliva and the Paradoxical Protective Role of Saliva -- Chapter 2 - Oral Bacteria Transmissible by Saliva and Kissing -- Chapter 3 - Systemic Bacteria Transmissible by Kissing -- Chapter 4 - Viral Diseases Transmissible by Kissing -- Chapter 5 - Fungi, Protozoa, Parasites, and Other Infective Agents Transmissible by Kissing
Includes bibliographical references.
Keywords: Saliva -- Microbiology; Communicable diseases -- Pathogenesis; Communicable diseases -- Transmission; Communicable diseases -- Microbiology; Electronic book